PENERAPAN METODE PEMBELAJARAN QUANTUM LEARNING UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN METAKOGNITIF KONSEP SISTEM GERAK MANUSIA PADA SISWA KELAS XI IPA SMA NEGERI 10 AMBON - Jean Lekatompessy; Hasan Tuaputty; Prelly M. J Tuapattinaya (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2020)
Lising of exact teaching method, is an alterative to overcome the weakness of student is reserve live to the lesson, in order to promote the quality of the teaching learning method Quantum learning is kinds of methods or philosophy for learning speed, (accelereted learning) accelerated learning can be define as the way to suport students in learning with wondrful accelerated, by using normal evort and anthusiastie this research is aim to know the implementation promote learning method Quantum learning in order to promote learning result and metacognitive concept of human movement system to the students in class XI IPA2 SMA Negeri 10 Ambon. This kind of research using descriptive research subject is the class IPA2 which capacity 26 students. Data of biology learning result is obtained through out pre test and post test, observation is used to observe cognitive ability, afeecitve, and psycomotor. The result of research is obtained in avarage of finally score 89,09% and metacognitive skill in pre test in average 51,69% and post test 93,88%.